2023
DOI: 10.1093/cid/ciad368
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Immunoglobulin Products Contain Neutralizing Antibodies Against Severe Acute Respiratory Syndrome Coronavirus 2 Spike Protein

Abstract: Background Patients with antibody deficiency respond poorly to COVID-19 vaccination and are at risk of severe or prolonged infection. They are given long-term immunoglobulin replacement therapy (IRT) prepared from healthy donor plasma to confer passive immunity against infection. Following widespread COVID-19 vaccination alongside natural exposure, we hypothesised that immunoglobulin preparations will now contain neutralising SARS-CoV-2 spike antibodies which confer protection against COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Our observations are consistent with those of previous trials of antibody-based therapies—administration of sufficient pathogen-specific antibodies via COVID-19 convalescent plasma leads to a reduced risk of disease progression, COVID-19-related hospitalization, and COVID-19-related death in immunocompromised patients in both outpatient and inpatient settings ( 5 , 19 ). Collectively, contemporary clinical data provide evidence to support the utility of high-titer convalescent plasma including vax-plasma as antibody replacement therapy in immunocompromised patients ( 17 , 20 , 21 ).…”
Section: Resultsmentioning
confidence: 93%
“…Our observations are consistent with those of previous trials of antibody-based therapies—administration of sufficient pathogen-specific antibodies via COVID-19 convalescent plasma leads to a reduced risk of disease progression, COVID-19-related hospitalization, and COVID-19-related death in immunocompromised patients in both outpatient and inpatient settings ( 5 , 19 ). Collectively, contemporary clinical data provide evidence to support the utility of high-titer convalescent plasma including vax-plasma as antibody replacement therapy in immunocompromised patients ( 17 , 20 , 21 ).…”
Section: Resultsmentioning
confidence: 93%
“…5,19 Collectively, contemporary clinical data provide evidence to support the utility of high-titer convalescent plasma including vax-plasma as antibody replacement therapy in immunocompromised patients. 17,20,21…”
Section: Resultsmentioning
confidence: 99%
“…The antivirals Paxlovid (nirmatrelvir/ritonavir), remdesivir, and molnupiravir continue to be recommended, having significantly reduced hospitalisation and death with early variants and showing benefits in secondary endpoints such as time to recovery with the Omicrom variant [ 96 , 97 , 98 ]. With regards to supporting humoral immunity, studies of commercial immunoglobulin products have demonstrated substantial levels of anti-SARS-CoV-2 IgG present, sufficient to match values found in convalescent and vaccinated individuals once administered, with one study highlighting a large increase of the antibodies in patient sera post-administration in 35 individuals [ 99 , 100 , 101 ]. This latter study also demonstrated viral clearance following initiation of IgRT after a median of 20 days in antibody-deficient patients with pre-existing prolonged COVID-19 (median 189 days, maximum > 900 days) [ 100 ].…”
Section: Covid-19mentioning
confidence: 99%
“…With regards to supporting humoral immunity, studies of commercial immunoglobulin products have demonstrated substantial levels of anti-SARS-CoV-2 IgG present, sufficient to match values found in convalescent and vaccinated individuals once administered, with one study highlighting a large increase of the antibodies in patient sera post-administration in 35 individuals [ 99 , 100 , 101 ]. This latter study also demonstrated viral clearance following initiation of IgRT after a median of 20 days in antibody-deficient patients with pre-existing prolonged COVID-19 (median 189 days, maximum > 900 days) [ 100 ]. As one might expect due to widespread vaccination and post-infection immunity, the amount of anti-SARS-CoV-2 IgG present in immunoglobulin products appears to be increasing, suggesting increased protection for patients receiving the therapy moving forwards [ 102 ].…”
Section: Covid-19mentioning
confidence: 99%